A randomized controlled study to evaluate the effect of bexarotene on amyloid‐β and apolipoprotein E metabolism in healthy subjects. Issue 2 (17th June 2016) - Ghosal, Kaushik; Haag, Michael; Verghese, Philip B.; West, Tim; Veenstra, Tim; Braunstein, Joel B.; Bateman, Randall J.; Holtzman, David M.; Landreth, Gary E.
Abstract: Introduction: We conducted a phase Ib proof of mechanism trial to determine whether bexarotene (Targretin) increases central nervous system (CNS) apolipoprotein E (apoE) levels and alters Aβ metabolism in normal healthy individuals with the APOE ε3/ε3 genotype. Methods: We used stable isotope labeling kinetics (SILK‐ApoE and SILK‐Aβ) to measure the effect of bexarotene on the turnover rate of apoE and Aβ peptides and stable isotope spike absolute quantitation (SISAQ) to quantitate their concentrations in the cerebrospinal fluid (CSF). Normal subjects were treated for 3 days with bexarotene (n = 3 women, 3 men, average 32 years old) or placebo (n = 6 women, average 30.2 years old) before administration of C 13 ‐leucine and collection of plasma and CSF over the next 48 hours. Bexarotene concentrations in plasma and CSF were also measured. Results: Oral administration of bexarotene resulted in plasma levels of 1 to 2 μM; however, only low nM levels were found in CSF. Bexarotene increased CSF apoE by 25% but had no effect on metabolism of Aβ peptides. Discussion: Bexarotene has poor CNS penetration in normal human subjects. Drug treatment resulted in a modest increase in CSF apoE levels. The absence of an effect on Aβ metabolism is likely reflective of the low CNS levels of bexarotene achieved. This study documents the utility of SILK‐ApoE technology in measuring apoE kinetics in humans. Trial Registration: This trial is registered at clinicaltrials.gov (NCT02061878 ).